Viability of the use of an A-SiC:H multiplayer device in a domestic VLC application - Louro, Paula (2015)
In this paper the viability of an integrated wavelength optical filter and photodetector for visible light communication (VLC) is discussed. The proposed application uses indoor warm light lamps lighting accomplished by ultra-bright light-emitting diodes (LEDs) pulsed at frequencies higher than the ones perceived by the human eye. The system was analyzed at two different wavelengths in the visible spectrum (430 nm and 626 nm) with variable optical intensities. The signals were transmitted into free space and measured using a multilayered photodetector based on a-SiC:H/a-Si:H. The detector works as an optical filter with controlled wavelength sensitivity through the use of optical bias. The output photocurrent was measured for different optical intensities of the transmitted optical signal and the extent of each signal was tested. The influence of environmental fluorescent lighting was also analysed in order to test the strength of the system. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.